'Magic mothers and wicked criminals': Exploring narrative and role in a drama programme with women prisoners. Issue 1 (1st January 2013) - Woodland, Sarah
This article explores narrative and role as key elements of an applied theatre project with women in an Australian prison. The research story has arisen out of the first stages of data analysis from the project, where a range of sometimes conflicting narratives and roles emerged as prevalent within the workshop process itself, as well as its surrounds; and where narrative and role helped to articulate the complexity of the applied theatre practice/research experience. The practice and research methodologies for the project were inextricably entwined, furthering James Thompson's (2003) notion of 'theatre action research' and Hughes et al.'s (2011) 'practised method'. These practitioner/researchers recognize applied theatre as both the process and the object of inquiry, a dynamic relationship that complicates both the research narrative and the roles played within it.